Amides as Non-polymerizable Catalytic Adjuncts Enable the Ring-Opening Polymerization of Lactide With Ferrous Acetate Under Mild Conditions - Naolou, Toufik; Lendlein, Andreas; Neffe, Axel T. (Frontiers in Chemistry, 2019)
Sn-based catalysts are effective in the ring-opening polymerization (ROP) but are toxic. Fe(OAc)2 as alternative catalyst is suitable for the ROP of lactide only at higher temperatures (>170 °C), associated with racemization. In the ROP of ester and amide group containing morpholinediones with Fe(OAc)2 to polydepsipeptides at 135 °C, ester bonds were selectively opened. Here, it was hypothesized that ROP of lactones is possible with Fe(OAc)2 when amides are present in the reactions mixture that as Fe-ligands could increase the solubility and activity of the metal catalytic center. The ROP of lactide in the melt with Fe(OAc)2 is possible at temperatures as low as 105 °C in the presence of N-ethylacetamide or N-methylbenzamide as non-polymerizable catalytic adjuncts (NPCA) with high conversion (up to 99 mol%) and yield (up to 88 mol%). Polydispersities of polylactide decreased with decreasing reaction temperature to ≤1.1. NMR as well as polarimetric studies showed that no racemization occurred at reaction temperatures ≤145 °C. A kinetic study demonstrated a living chain-growth mechanism. MALDI analysis revealed that no side reactions (e.g. cyclization) occurred, though transesterification took place.